Exclusive breastfeeding duration and its influence on preventing childhood stunting - Pipit Feriani; Candra Kusuma Negara; Rini Ernawati (Universitas Airlangga, 2026)
Introduction: Childhood stunting represents a major global health challenge affecting 149 million children under five years worldwide. Exclusive breastfeeding has been identified as an important protective factor in stunting prevention, yet empirical evidence regarding this relationship in Indonesian primary healthcare settings remains limited. This study aimed to analyze the relationship between exclusive breastfeeding history and stunting occurrence among children aged 7-59 months at UPTD Loa Ipuh Primary Healthcare Center.Methods: This cross-sectional study involved 120 mothers with children aged 7-59 months in the UPTD Loa Ipuh catchment area, Kutai Kartanegara Regency, East Kalimantan. Consecutive sampling was employed for participant recruitment. Data were collected through structured interviews using a validated questionnaire. Chi-square tests were used to determine the association between exclusive breastfeeding and stunting occurrence.Results: Of 120 participants, 58.3% of children received exclusive breastfeeding while 41.7% did not receive exclusive breastfeeding. The overall stunting prevalence was 50.0%, with 12.5% severely stunted and 37.5% stunted. Chi-square test results demonstrated a statistically significant association between exclusive breastfeeding history and stunting occurrence (P-value = .01). Children who did not receive exclusive breastfeeding showed higher prevalence of severe stunting (22.0%) compared to those who received exclusive breastfeeding (5.7%). Conversely, children who received exclusive breastfeeding had a higher proportion of normal nutritional status (58.6%) compared to those who did not receive exclusive breastfeeding (38.0%).Conclusion: Exclusive breastfeeding proves to be a significant protective factor against childhood stunting, with up to four-fold reduction in severe stunting risk. These findings support the importance of exclusive breastfeeding promotion as a cost-effective intervention in stunting prevention, though it should be integrated within holistic approaches that comprehensively address multiple determinants of stunting.Keywords: exclusive breastfeeding, stunting, nutritional status, children under five, primary healthcare